Neutropenia in rheumatoid arthritis and large granular lymphocyte leucosis - V A Doronin; E A Nikitin; J. V. Sidorova; A. V. Pivnik (Научно-практическая ревматология)
Objective. Pts with chronic clonal proliferation of large granular lymphocytes (LGL leukemia) often have neutropenia, splenomegaly, and rheumatoid arthritis (RA), thereby resembling the manifestations observed in pts with Felty’s syndrome. The present study sought to indicate that pts with these disorders represent two distinct subsets. We compare clinical, hematological, immunophenotiping and immunogenetic features in Felty’s syndrome pts with and without the LGL leukemia. Material and methods 10 pts with T-LGL leukemia were studied. Surface phenotype was estimated using monoclonal antibodies CD8-PE and CD3-FITC/CD16-PE (two-color) (Caltag, USA) by the flow cytometric analysis (Partec, Daco). Analysis of TCR gene rearrangement was performed by using PCR-LIS SSCP (low ionic strength single strand conformational polymorphism). Comparison with Felty s syndrome and RA pts based on the review of literature. Results. LGL leukemia is a distinct clinicopathologic entity often associated with RA. LGL leukemia pts with RA showed the same immunogenetis associations seen in RA/Felty’s syndrome, while LGL leukemia pts without arthritis did not. Conclusion. Hematologic, immunophenotyping and molecular genetic analysis are very important and highly representative tools in differential diagnosis of neutropenia in RA, and propose that Felty’s syndrome and LGL leukemia represent different variants of broader syndrome comprising RA, neutropenia, LGL expansions, and splenomegaly.